Analisis Pendapatan Dan Strategi Pengembangan Cabai Merah Di Desa Tibo Kecamatan Sindue Kabupaten Donggala - Muhammad Arsyd; Saiful Darman; Lien Damayanti (Agroland: Jurnal Ilmu-ilmu Pertanian, 2018)
ABSTRACT The objectives of the research was to discover the income of farmers and to determine the development strategy of red chili farming system in Tibo village of Donggala district, Central Sulawesi.   Respondents of twenty three family heads who have been cultivating red chilli were selected from farmer population along with five stakeholders, three local extension workers, and the head of the village. Data collected was gathered through observation, interview and Focus Group Discussion (FGD).  The average income of the red chili farming system was found to be IDR 19,471,130/ha/planting season, while the R/C ratio was 3.90.  These results suggested that the red chilli farming is very profitable to be developed. The Strength Weakness Opportunities and Threats (SWOT) analysis showed that the strategy of developing the red chilli farming in Tibo village was positioned in the quadrant II indicating Strength-Threats strategy to support diversification strategy.  These strategies include:  (1) to increase the availability of potential land and to make the most of the manpower availability for the development of this potential commodity (red chilli), and (2) to take advantage of the experience and high motivation of the farmers as well as to improve the farmer knowledge.  The Quantitative Strategic Planning Matrix (QSPM) analysis indicated that the second strategy is the most feasible program that could be implemented with the total value of attractiveness (TAS) was highest (6.624) Keywords: Development Strategy, Income Analysis, Red Chili.